Babala and the Bible: Israel and a 'Messianic Church' in Papua New Guinea. Issue 3 (15th October 2015) - Dundon, Alison
Abstract: In early 2000s, a large group of Gogodala‐speaking villagers in the Western Province (WP) of Papua New Guinea, led by a man I refer to as Henry, claimed to be members of the Lost Tribes of Israel. Henry and his supporters arranged for the visit of Tudor Parfitt, then Director of the Centre for Jewish Studies at the University of London, to WP. In this paper, I suggest that an ongoing local interest in 'origins' has been framed in light of biblical teachings, and this more recent claim of a connection between the Gogodala ancestors and the Lost Tribes of Israel. I explore the generation of such ideas and claims through an examination of the significance of babala ('rules' or 'laws') as practices vital to the maintenance of village‐based life, and biblical teachings on behaviour and practice focused on by the local Unevangelised Fields Mission. In this context, I explore the implications of the conjuncture of babala and the Bible, and the visits by Parfitt and his team, through the recent development of a 'Messianic Church' in Balimo with explicit forms of worship associated with Judaism.